High‐fat diet induces protein kinase A and G‐protein receptor kinase phosphorylation of β2‐adrenergic receptor and impairs cardiac adrenergic reserve in animal hearts. (2nd February 2017) - Fu, Qin; Hu, Yuting; Wang, Qingtong; Liu, Yongming; Li, Ning; Xu, Bing; Kim, Sungjin; Chiamvimonvat, Nipavan; Xiang, Yang K.
Abstract : Key points: Patients with diabetes show a blunted cardiac inotropic response to β‐adrenergic stimulation despite normal cardiac contractile reserve. Acute insulin stimulation impairs β‐adrenergically induced contractile function in isolated cardiomyocytes and Langendorff‐perfused hearts. In this study, we aimed to examine the potential effects of hyperinsulinaemia associated with high‐fat diet (HFD) feeding on the cardiac β2 ‐adrenergic receptor signalling and the impacts on cardiac contractile function. We showed that 8 weeks of HFD feeding leads to reductions in cardiac functional reserve in response to β‐adrenergic stimulation without significant alteration of cardiac structure and function, which is associated with significant changes in β2 ‐adrenergic receptor phosphorylation at protein kinase A and G‐protein receptor kinase sites in the myocardium. The results suggest that clinical intervention might be applied to subjects in early diabetes without cardiac symptoms to prevent further cardiac complications. Abstract: Patients with diabetes display reduced exercise capability and impaired cardiac contractile reserve in response to adrenergic stimulation. We have recently uncovered an insulin receptor and adrenergic receptor signal network in the heart. The aim of this study was to understand the impacts of high‐fat diet (HFD) on the insulin–adrenergic receptor signal network in hearts. After 8 weeks of HFD feeding, mice exhibited diabetes, with elevated insulin and glucose concentrations associated with body weight gain. Mice fed an HFD had normal cardiac structure and function. However, the HFD‐fed mice displayed a significant elevation of phosphorylation of the β2 ‐adrenergic receptor (β2 AR) at both the protein kinase A site serine 261/262 and the G‐protein‐coupled receptor kinase site serine 355/356 and impaired adrenergic reserve when compared with mice fed on normal chow. Isolated myocytes from HFD‐fed mice also displayed a reduced contractile response to adrenergic stimulation when compared with those of control mice fed normal chow. Genetic deletion of the β2 AR led to a normalized adrenergic response and preserved cardiac contractile reserve in HFD‐fed mice. Together, these data indicate that HFD promotes phosphorylation of the β2 AR, contributing to impairment of cardiac contractile reserve before cardiac structural and functional remodelling, suggesting that early intervention in the insulin–adrenergic signalling network might be effective in prevention of cardiac complications in diabetes. Key points: Patients with diabetes show a blunted cardiac inotropic response to β‐adrenergic stimulation despite normal cardiac contractile reserve. Acute insulin stimulation impairs β‐adrenergically induced contractile function in isolated cardiomyocytes and Langendorff‐perfused hearts. In this study, we aimed to examine the potential effects of hyperinsulinaemia associated with high‐fat diet (HFD) feeding on the cardiac β2 ‐adrenergic receptor signalling and the impacts on cardiac contractile function. We showed that 8 weeks of HFD feeding leads to reductions in cardiac functional reserve in response to β‐adrenergic stimulation without significant alteration of cardiac structure and function, which is associated with significant changes in β2 ‐adrenergic receptor phosphorylation at protein kinase A and G‐protein receptor kinase sites in the myocardium. The results suggest that clinical intervention might be applied to subjects in early diabetes without cardiac symptoms to prevent further cardiac complications.